John F. Kennedy, the president that the media created and loved - Piotrowski, Maciej (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
John Kennedy is one of the most popular presidents in American history. There are a number of factors that have contributed to this fact. The origins of his fame can be traced back to the 1960 presidential campaign. It was then that the first ever television debate between the presidential candidates – Richard Nixon vs. John Kennedy – was organized. During the debate, JFK presented a huge class – he looked great, used the right body language, was incredibly calm. In every element he proved to be better than his rival in the fight for the highest state office. The debate broadcasted by the television determined the fate of the election results. After winning the election, Kennedy became an incredibly popular person – the media loved him. One can certainly argue that John Kennedy was the president that the media created and loved. His mediality was influenced, among others, by childhood events – he grew up in a house where film stars were often present. He wasn’t even harmed by the stormy romance with Marilyn Monroe. It is also noteworthy that after his tragic death in Dallas Kennedy he was and still is present in the world media discourse – films, novels and even computer games with his characters started to be made. In writing the article I used a historical research method combined with the study of media discourse.